Human development and its affect on eco-tourism development in Islamic society from geographical aspects: An empirical study in Sabrata, Libya / Fouziyah Alsadiq Ahmed Alamouri - Fouziyah Alsadiq, Ahmed Alamouri (2019)
The aim of this study is to achieve a number of objectives, the most important of which is to identify the impact of human development indicators including education, health, services and income in the development of ecotourism. It also sheds light on the importance of ecotourism by highlighting a range of offered dimensions such as environmental, social and economic. These dimensions cumulatively allow the development of an encouraging ecotourism society. The study includes the importance of relating the study of tourism to its application in the Islamic societies to clarify its Sharia governing rules in this regard. The study also establishes the importance as well as the reality of development in the Islamic societies. This study adopts a descriptive approach in order to describe and analyze the research data quantitatively and qualitatively. In this respect, a questionnaire is used to illustrate the impact of human development indicators on the development of the ecotourism in the Libyan society (of the City of Sabratha). The research sample includes 425 participants from the local residents, employees of the tourism sector as well as local and foreign tourists. To analyze the research data and to reach to the results that achieve the research purposes, the researcher integrates statistical methods such as Cronbach’s Alpha, T-Test, and Anova. A descriptive analysis is carried on the demographic variables as well as the Simple Linear Regression, and the examination of the correlation between the independent variables on the dependent variable. The study reaches to a set of results that in turn realizes the research hypotheses. The research findings establish that there is an important and effective impact of education, health, services and income on the development of ecotourism. The study also includes a number of recommendations which can be implemented on the ground and achieve ecotourism development according to the scientific standards.